2012
DOI: 10.3233/wor-2012-1306
|View full text |Cite
|
Sign up to set email alerts
|

Health information management in the home: A human factors assessment

Abstract: Objective: Achieving optimal health outcomes requires that consumers maintain myriad health data and understand how to utilize appropriate health information management applications. This case study investigated four families' health information management tasks in their homes. Participants: Four different families participated in the study: a single parent household; two nuclear family households; and an extended family household. Methods: A work system model known as the balance model was used as a guiding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Our work contributes to a growing body of research in personal health information management and personal health information tracking—research that has already identified a range of tasks frequently performed by patients, ranging from tracking health data to managing medical records to creating personal reminder systems [ 27 - 29 , 31 , 32 ]. However, much of the previous work in this field has focused on generally healthy individuals and families [ 27 , 28 , 31 , 32 ], on patients with cancer [ 33 - 36 ], or (in support of HIT design) on computer-literate participants [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work contributes to a growing body of research in personal health information management and personal health information tracking—research that has already identified a range of tasks frequently performed by patients, ranging from tracking health data to managing medical records to creating personal reminder systems [ 27 - 29 , 31 , 32 ]. However, much of the previous work in this field has focused on generally healthy individuals and families [ 27 , 28 , 31 , 32 ], on patients with cancer [ 33 - 36 ], or (in support of HIT design) on computer-literate participants [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support previous work in the field of technology development for elderly patients or others who do not use electronic technologies regularly. The people we spoke with conducted personal health information management and tracking with a variety of paper and electronic tools, both custom-made and adapted, as has been found by other researchers [ 27 , 29 , 31 ]. As others have found, we found that older patients and those with Medicaid were frequently unfamiliar with electronic technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Attending the diabetes education group for ongoing triangulation and relying on the group for the member check could have made the final themes more representative of patients with diabetes than of patients with other chronic conditions. Our focus on information being used by patients in their interactions with the medical system also means that the types of medical information being discussed was probably narrower than the broader range described in some other PHIM literature [ 22 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found that individuals use both custom-made tools (such as electronic patient portals) as well as paper and pencil and a variety of other artifacts. Others have noted that patients use commercial calendars to track medical appointments, post medication checklists on refrigerator doors, or intermingle pediatric immunization records with memorabilia about the child’s milestones [ 22 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating research on PHIM from the perspective of patients demonstrates the "work" it takes to manage personal health information outside the clinic in everyday life (3,5,38,(40)(41)(42)(43). PHIM needs are well documented for some groups, such as people experiencing cancer (44)(45)(46) or chronic illness (38,47), but less specifically for older adults (9).…”
Section: Introductionmentioning
confidence: 99%